2019
DOI: 10.1111/jocd.13113
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet‐rich plasma therapy for pattern hair loss: A systematic review

Abstract: Background Androgenetic alopecia (male pattern and female pattern hair loss) is characterized by thinning of the scalp hair. Intradermal injection of autologous platelet‐rich plasma (PRP) might have an effect on hair regrowth. Aims The aim was to evaluate efficacy and safety of platelet‐rich plasma compared to placebo or no treatment in people with pattern hair loss. Patients/Methods We searched the databases CENTRAL and MEDLINE on December 24, 2018 and included randomized controlled trials (RCTs). Primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…Fifteen references matched the inclusion criteria and were included in the present method study 1–15. In five systematic reviews,4,6,8,13 we identified various overt methodological inconsistencies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen references matched the inclusion criteria and were included in the present method study 1–15. In five systematic reviews,4,6,8,13 we identified various overt methodological inconsistencies.…”
Section: Resultsmentioning
confidence: 99%
“…This result would indicate an astounding absence of heterogeneity, which does not appear to make much sense considering the inclusion of various types of study designs and comparisons. For example, Mao et al12 reported an I 2 value of 63% in a meta‐analysis of four RCTs, and Dervishi et al1 reported an I 2 value of 100% in a meta‐analysis of seven RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both techniques cause microtrauma that induces neovascularization, collagen formation, and stimulation of growth factors to increase hair growth and thickness (Figure 3). 6,[40][41][42] Adipose tissue, which is a source of mesenchymal stem cells, can be injected into the scalp as a treatment option for FPHL. This therapy allows for the release of growth factors and angiogenesis to induce hair growth.…”
Section: Treatmentmentioning
confidence: 99%